The Situation of Antibiotic Resistance of Bacteria Isolated from Fresh Water Fish in Hai Duong Province - Giang, Nguyen Thi; Ngoc, Pham Duc; Hanh, Tran My; Ha, Bui Thi Viet (VNU Journal of Science: Natural Sciences and Technology, 2016)
Abstract:  In aquaculture, antibiotics have been used mainly for therapeutic purposes and as prophylactic agents. The abuse of antibiotics in aquaculture farming is a big problem. To achieve high yields and profits, many farmers are now applying intensive farming methods. The improper use of antibiotics causes the phenomenon of drug-resistant bacteria and residue accumulation of antibiotics in aquatic meat. Another reason causing antibiotics-resistant bacteria is the use of antibiotics to small quantities of aquatic feed as a growth stimulant. So that in this study, the initial evaluation of the antibiotic resistance of bacteria isolated from freshwater fish was determined. The experimental results showed that 33/36 strains isolated from fish samples were resistant to 8 types of antibiotics reached 91%. Most of them are multi-drug resistant strains. They are capable of resisting two or more antibiotics. Especially, C23 strain, belong to Pseudomonas monteilii species, was capable of resisting to all 8 antibiotics. This strain shows the ability to withstand the temperature and pH range and can use a wide variety of different nutrients. Keywords: Antibiotic resistance , Pseudomonas monteilii, freshwater fish.